The Relationship of Amount of Pleural Fluid and Time of Pleurodesis with the Results of Pleurodesis in Malignant Pleural Effusions - Sutanto, Yusup Subagio; Sigit, Indarto; Kurniawan, Hendra (Indonesian Journal of Medicine, 2020)
Background: Pleural effusion can be an early sign of lung cancer in more than 25% of cases. Lung cancer is the most common cause of malignant pleural effusion (MPE). Pleurodesis is performed when the amount of pleural fluid is <150 ml/day, but it is difficult as its productive nature. This study aimed to find the right time to perform pleurodesis on patients with MPE, which is expected to achieve optimal results.Subjects and Method: This was a cross-sectional study conducted at Dr. Moewardi Hospital, Surakarta, Central Java, from June to July 2020. The study subjects were 17 patients with malignant pleural effusion (MPE) diagnosed with lung cancer who underwent water seal drainage (WSD) and indicated for pleurodesis. The dependent variable was the success of the pleurodesis procedure. The independent variables were the amount of evacuated pleural fluid and the time of pleurodesis performed. The study instruments were diagnosis of lung cancer with anatomic pathology, measurement of the amount of pleural fluid, and posteroanterior chest X-ray evaluating the success of pleurodesis. The data were analyzed using Spearman correlation, ANOVA to determine the differences in the amount of pleural fluid at the first, second, and third hours, and continued with post hoc LSD analysis using SPSS 21.Results: The pleurodesis success rate had positive correlation with the amount of pleural fluid (r= 0.24; p= 0.345) and the time of pleurodesis performed at the first hour (r= 0.10; p= 0.701), second hour (r= 0.03; p= 0.921), and third hour (r= 0.41; p= 0.106). Pleurodesis performed at the second hour had the lowest amount of pleural fluid (Mean= 84.66; SD= 38.88), followed by third hour (Mean= 110.77; SD= 65.57), and first hour (Mean= 111.22; SD= 57.83), but the differences were not statistically significant (p= 0.285).Conclusion: The pleurodesis success rate has a positive correlation with the amount of pleural fluid and the time of pleurodesis, but it was not statistically significant. There is no significant difference in the amount of pleural fluid evacuated at the three different times of pleurodesis. The least amount of pleural fluid obtains at the second hour (14.00-22.00).Keywords: malignant pleural effusion, amount of pleural fluid, pleurodesis, pleurodesis timeCorrespondence: Yusup Subagio Sutanto. Department of Pulmonology and Respiratory Medicine, Faculty of Medicine Universitas Sebelas Maret, Dr. Moewardi Hospital, Surakarta. Jl. Kolonel Sutarto 132, Surakarta 57126, Central Java. Email: dr_yusupsubagio@yahoo.com. Mobile: +62811284165.Indonesian Journal of Medicine (2020), 05(04): 337-342https://doi.org/10.26911/theijmed.2020.05.04.09.